The Concept of Operational Near Real-Time GNSS Meteorology System for Atmospheric Water Vapour Monitoring over Peninsular Malaysia - Norazmi, Muhammad Faiz Bin (Springer Verlag, 2015)
The operational system from near real-time global navigation satellite system (NRT GNSS) meteorology is crucial for supplying information about climate and meteorological activities over Malaysia. As demonstrated by many researchers all over the world, the applicability of NRT GNSS meteorology has proved as a valuable tool for capturing high spatio-temporal resolution of atmospheric water vapour. This study discusses a design of NRT GNSS meteorology system for future development in Malaysia. There are three major components of this system which cover the architecture of GNSS meteorological station, the engine processor and data flow management. This paper provides the functional illustration for each component and discusses several challenges in the development of NRT GNSS meteorology system.